Reservation Wages and the Wage Flexibility Puzzle - Felix Koenig; Alan Manning; Barbara Petrongolo (Institute for the Study of Labor (IZA), 2016)
Wages are only mildly cyclical, implying that shocks to labour demand have a larger short-run impact on unemployment rather than wages, at odds with the quantitative predictions of the canonical search model – even if wages are only occasionally renegotiated. We argue that one source of the wage flexibility puzzles is plausibly the model for the determination of reservation wages, and consider an alternative reservation wage model based on reference dependence in job search. This extension generates less cyclical reservation wages than the canonical model, as long as reference points are less cyclical than forward-looking components of reservation wages such as the arrival rate of job offers. We provide evidence that reservation wages significantly respond to backward-looking reference points, as proxied by rents earned in previous jobs. In a model calibration we show that backward-looking reference dependence markedly reduces the predicted cyclicality of both wages and reservation wages and can reconcile theoretical predictions of the canonical model with the observed cyclicality of wages and reservation wages.
Keywords: E24; J31; J64; 330; job search; reservation wages; wage cyclicality; reference dependence